2011
DOI: 10.1371/journal.pone.0029600
|View full text |Cite
|
Sign up to set email alerts
|

Trans Fatty Acids Induce Vascular Inflammation and Reduce Vascular Nitric Oxide Production in Endothelial Cells

Abstract: Intake of trans fatty acids (TFA), which are consumed by eating foods made from partially hydrogenated vegetable oils, is associated with a higher risk of cardiovascular disease. This relation can be explained by many factors including TFA's negative effect on endothelial function and reduced nitric oxide (NO) bioavailability. In this study we investigated the effects of three different TFA (2 common isomers of C18 found in partially hydrogenated vegetable oil and a C18 isomer found from ruminant-derived—dairy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 30 publications
5
71
1
2
Order By: Relevance
“…The diet high in hydrogenated fat increased production of inflammatory cytokines. Higher intakes of TFA increased concentrations of inflammatory molecules such as interleukin-6, tumor necrosis factor-α, C-reactive protein, and monocyte chemo attractant protein-1 (Iwata et al 2011).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The diet high in hydrogenated fat increased production of inflammatory cytokines. Higher intakes of TFA increased concentrations of inflammatory molecules such as interleukin-6, tumor necrosis factor-α, C-reactive protein, and monocyte chemo attractant protein-1 (Iwata et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Oxidative stress is considered to be an important promoter for inflammation (Iwata et al 2011). Some of the oxidative stress markers can be monitored in liver.…”
Section: Discussionmentioning
confidence: 99%
“…Repeatedly heated oils at high temperature will undergo chemical conversion of fatty acid configuration from cis to trans isomer [28]. Diets containing trans fatty acid could be detrimental to cardiovascular health because it was reported that this fatty acid isomer could induce inflammation of the blood vessels and decrease its nitric oxide production [29][30]. The polymer and polar compounds content are also increased more than 37% and 47% respectively when the oil is used to fry [31].…”
Section: Discussionmentioning
confidence: 99%
“…Trans fatty acids reduce endothelial nitric oxide production in vitro, 54 and thus may have detrimental effects on vascular function. However, our data do not support a statistically significant association of long-term trans fatty acid intake with vascular function (as assessed by PAT) in our sample.…”
Section: Trans Fatty Acidsmentioning
confidence: 99%